Multi-screen and multi-device game development - Mendez, P. S. (2018)
Users are interacting with an increasing number of devices and screens. However, these screens are usually used independently without collaboration between them. Although there have been several advances in multi-screen applications the game community does not seem to have fully explored this opportunity as yet. This paper presents an approach for the development of mobile multi-screen and multi-device games. The approach aims to enable and foster the creation of multi-device games sharing information via a centralized screen and is demonstrated by means of an example, the well-known Casino Roulette game. The results of a preliminary evaluation of the game are also presented.